Hidden Diversity in the Populations of the Armored Catfish Ancistrus Kner, 1854 (Loricariidae, Hypostominae) from the Paraná River Basin Revealed by Molecular and Cytogenetic Data - Prizon, Ana C.; Bruschi, Daniel P.; Borin-Carvalho, Luciana A.; Cius, Andréa; Barbosa, Ligia M.; Ruiz, Henrique B.; Zawadzki, Claudio H.; Fenocchio, Alberto S.; Portela-Castro, Ana L. de Brito (Frontiers in Genetics, 2017)
Only one species of armored catfish, Ancistrus cirrhosus Valenciennes 1836, has been historically described in the basin of the Paraná River, from Misiones (Argentina). However, the ample variation found in the morphology and coloration of the populations sampled in the tributaries of the Brazilian state of Paraná makes it difficult to establish the real taxonomic status and evolutionary history of the Ancistrus specimens, suggesting that Ancistrus cirrhosus is not the only species found in this basin. By combining data on mitochondrial DNA (COI gene) and chromosomal markers from different Ancistrus populations, totaling 144 specimens, in the tributaries of the Paraná, and specimens from Misiones (type-locality of A. cirrhosus), we detected five distinct evolutionary lineages. All the specimens were 2n=50, but had four distinct karyotype formulae. The results of the Generalized Mixed Yule Coalescent (GYMC) and the genetic distances (uncorrected P values) between lineages ranged from 3% to 5%. Clusters of 18S rDNA were observed in a single chromosome pair in seven populations of Ancistrus, but at different positions, in some cases, in synteny with the 5S rDNA sites. Multiple 5S sites were observed in all populations. Overall, the cytogenetic data reinforce the genetic evidence of the diversification of lineages, and indicate the existence of candidate species in the study region. The evidence indicates that at least four candidate species of the Ancistrus may coexist in the Paraná basin besides A. cirrhosus. Overall, our results provide a comprehensive scenario for the genetic variation among Ancistrus populations and reinforce the conclusion that the true diversity of the freshwater fish of the Neotropical regions has been underestimated.